Comparison of the Effectiveness of Cognitive-Behavioral Couple Therapy and Schema Therapy on Improving Communication Patterns in Couples Affected by Domestic Violence - Talaei Kahjugh, Mohammad; Nikmanesh, Arash; Pourmohammad Ghouchani, Kamran (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of Schema Therapy and Cognitive-Behavioral Couple Therapy (CBCT) in improving communication patterns among couples affected by domestic violence.Methods and Materials: The study employed a quasi-experimental pretest-posttest design with a control group. The statistical population consisted of couples affected by domestic violence who referred to counseling centers in Tehran. A total of 45 participants were selected using simple random sampling and assigned to two experimental groups (Schema Therapy and CBCT) and one control group, each containing 15 participants. Data were collected using the Communication Patterns Questionnaire (Christensen & Salavy, 1984) and analyzed using multivariate analysis of covariance (MANCOVA) and Tukey’s post hoc test with SPSS version 26. Each intervention included 10 weekly sessions tailored to the specific therapeutic model.Findings: The MANCOVA results indicated statistically significant differences between groups in all three communication pattern dimensions: mutual constructive communication (F = 8.043, p < .01), mutual avoidant communication (F = 2.222, p < .05), and demand/withdraw communication (F = 1.068, p < .05). Tukey’s post hoc test revealed that Schema Therapy was significantly more effective than CBCT in improving mutual constructive communication (mean difference = 2.40, p = .006), reducing mutual avoidance (mean difference = 0.13, p = .000), and decreasing demand/withdraw patterns (mean difference = -1.00, p = .000).Conclusion: These findings suggest that Schema Therapy may offer deeper and more sustainable improvements in relational functioning by targeting underlying maladaptive schemas contributing to dysfunctional communication.